Incomplete stories for the development of critical and creative thinking in children (Revista Innova Educación, 2022)
The research objective was to design an incomplete story strategy model to develop critical and creative thinking in 4-year-old children. The research was basic propositional with a non-experimental design and a quantitative methodological approach. We worked with a sample of 92 children from the Initial Educational Institution No. 004 of Chiclayo (Lambayeque - Peru) who were randomly selected. A test on critical and creative thinking was developed and applied in which subdimensions and indicators were considered. This instrument was validated by expert judgment. As a result, it was found that more than half of the children had an average level of development of critical and creative thinking. Therefore, it was concluded that the proposed model is a novel contribution to education by allowing children to improve these thoughts when the said proposal is applied.
Keywords: incomplete stories; strategy; model; creative thinking; critical thinking